An experiment on the performance of shortest path algorithm - Chan, Simon Yew Meng; Adnan, Nur’ayuni; Sukri, Syazwan Syafiqah; Wan Zainon, Wan Mohd Nazmee (2016)
Shortest path algorithms are one of the main algorithms used in most navigation system. By implementing these algorithm, the related overall costs such as time and work load can be minimized. The main objective of this paper is to study and experiment the different shortest path algorithm such as Dijkstra’s algorithm, Symmetrical Dijkstra’s algorithm, A* algorithm, Bellman-Ford algorithm, Floyd-Warshall algorithm and Genetic algorithm in solving the shortest path problem. In this paper, a brief review on each of the shortest path algorithm and its implementation method was discussed.Explanation on how the experiment was conducted and the sample data that involved in the experiment were also presented. The result of the experiment shows the overall performance of each algorithm in solving shortest path problem in term of running time and total distances. The analysis of result shows the performance of each algorithm in order to suggest the most efficient algorithm in solving the shortest path problem